Higher premenopausal serum androgen levels and higher postmenopausal estrogen levels in women with endometrial hyperplasia - Kacalska-Janssen, Olga; Rajtar-Ciosek, Agnieszka; Zmaczyński, Andrzej; Milewicz, Tomasz; Bereza, Tomasz; Wiatr, Joanna; Krzysiek, Józef (Menopause Review/Przegląd Menopauzalny, 2012)
Objectives: To assess the hormonal status of individual groups of endometrial pathology. Prospective observational study. Material and methods: 100 peri- and postmenopausal women with abnormal uterine bleedings and/or abnormal endometrium. The population of women was divided into four groups according to hysteroscopic examination, confirmed by histopathology (non-atypical endometrial hyperplasia, polyp, cancer, controls). The levels of selected hormones, growth factors and binding proteins were marked. Results : Serum DHEAS, estradiol and estrone levels are significantly higher in women with hyperplasia in comparison with the control group (p < 0.05). Higher concentrations of serum DHEAS and testosterone occur more frequently in premenopausal women with hyperplasia (p < 0.01 and p < 0.05), whereas high concentrations of estradiol and estrone play an important role in the case of postmenopausal hyperplasia (p 5.58 ng/ml) occurred in 62.5% of women with endometrial hyperplasia, which suggests possible participation of this factor in the pathogenesis of hyperplastic changes of the endometrium. Conclusion: Higher serum androgen levels (DHEAS, testosterone) in premenopausal women with hyperplasia than in control group suggest possible participation of androgens in the pathogenesis of premenopausal hyperplasia, similarly to higher concentrations of estrogens (estradiol, estrone) in postmenopausal women.